2020
DOI: 10.3390/nu12020301
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gelatinized Wheat Starch and High Salt Diet on Gut Microbiota and Metabolic Disorder

Abstract: Diets high in gelatinized starch and high in gelatinized starch supplemented with salt-induced metabolic disorders and changes in gut microbiota have scarcely been studied. In this study, mice on wheat starch diets (WD) exhibited significantly higher body weight, white adipose tissue (WAT), and gut permeability compared to those on normal diet (ND). However, gelatinized wheat starch diet (GWD) and NaCl-supplemented gelatinized wheat starch diet (SGW) mice did not increase body and WAT weights or dyslipidemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
7
20
0
Order By: Relevance
“…For the microbiota, we discovered in the colon content of the mice similar results as described by Do et al (2020) [ 55 ], e.g., an increase in Muribaculaceae and a decrease in Lactobacillus in the gelatinized diet (E2) and decreased numbers for Muribaculaceae and increased numbers for Lactobacillus in P2, the diet with highest total starch content ( Figure 5 d). Other sampling regions in our experiment did not concord with the previous findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For the microbiota, we discovered in the colon content of the mice similar results as described by Do et al (2020) [ 55 ], e.g., an increase in Muribaculaceae and a decrease in Lactobacillus in the gelatinized diet (E2) and decreased numbers for Muribaculaceae and increased numbers for Lactobacillus in P2, the diet with highest total starch content ( Figure 5 d). Other sampling regions in our experiment did not concord with the previous findings.…”
Section: Discussionsupporting
confidence: 87%
“…Other sampling regions in our experiment did not concord with the previous findings. As Do et al (2020) [ 55 ] were using fecal samples for their study, the findings seem to be comparable to those found in the colons content and feces only. However, Do et al (2020) [ 55 ] did not provide data on the degree of starch gelatinization or dietary fiber in their diets, which makes a comparison with the data presented here difficult.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Bacteroides are salt-tolerant bacteria [ 50 ] and are associated with liver injury in human studies [ 51 , 52 ]. Animal studies also showed that the abundance of Proteobacteria and Bacteroides are higher in NAFLD [ 53 , 54 ]. Therefore, the increased abundance of Proteobacteria and Bacteroides may suggest liver damage and increased risk for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In other species little data is available on the association between these genera and lipid metabolism, steatosis and obesity. Several studies evidence increases in Romboutsia levels with obesity related metabolic disorders in humans [39] and in mice fed high fat [40] or high starch [41] diets, although no causal link has been established between this genus and obesity related traits to date. At first glance our results are in contrast with previous ones as Romboutsia levels are higher in birds with a positive response to spontaneous steatosis stimulation compared to overfed ones, despite a lower liver weight.…”
Section: Discussionmentioning
confidence: 99%